RESEARCH OF POWER GENERATOR PROTOTYPE DEVELOPMENT AND INTEGRATION INTO AUTONOMOUS ROBOTIC SYSTEMS - Matutis, Vaidotas; Savulioniene, Loreta; Sakalys, Paulius; Kasperavicius, Tomas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of the research is to perform experimental research based on patented technology to improve the efficiency and applicability of the patented invention in the power supply circuits of autonomous robotic systems in order to improve electricity utilization and regeneration rates, ensuring longer autonomous operation of the robotic system. The article reviews the technologies of electricity generation and aspects of their practical application. Described research methodology and research stand. Presented the results and conclusions of the performed simulation tests of the prototype electrodynamic parameters. Proposals made for the integration of research results into the students practical educational process.